Participation of the IL-10RB Related Cytokines, IL-22 and IFN-λ in Defense of the Airway Mucosal Barrier - Ahn, Danielle; Prince, Alice (Frontiers in Cellular and Infection Microbiology, 2020)
The airway epithelial barrier is a major barrier protecting against clinically significant infections of the lung. Its integrity is often compromised due to mechanical, chemical, or infectious causes. Opportunistic bacterial pathogens are poised to cause parenchymal infection and become difficult to eradicate due to adaptive metabolic changes, biofilm formation, and the acquisition of antimicrobial resistance and fitness genes. Enhancing mucosal defenses by modulating the cytokines that regulate barrier functions, such as interleukin-22 (IL-22) and interferon-λ (IFN-λ), members of the IL-10 family of cytokines, is an attractive approach to prevent these infections that are associated with high morbidity and mortality. These cytokines both signal through the cognate receptor IL-10RB, have related protein structures and common downstream signaling suggesting shared roles in host respiratory defense. They are typically co-expressed in multiple models of infections, but with differing kinetics. IL-22 has an important role in the producing antimicrobial peptides, upregulating expression of junctional proteins in the airway epithelium and working in concert with other inflammatory cytokines such as IL-17. Conversely, IFN-λ, a potent antiviral in influenza infection with pro-inflammatory properties, appears to decrease junctional integrity allowing for bacterial and immune cell translocation. The effects of these cytokines are pleotropic, with pathogen and tissue specific consequences. Understanding how these cytokines work in the mucosal defenses of the respiratory system may suggest potential targets to prevent invasive infections of the damaged lung.